Platinum coat color in red fox (Vulpes vulpes) is caused by a mutation in an autosomal copy of KIT. (6th February 2015) - Johnson, J. L.; Kozysa, A.; Kharlamova, A. V.; Gulevich, R. G.; Perelman, P. L.; Fong, H. W. F.; Vladimirova, A. V.; Oskina, I. N.; Trut, L. N.; Kukekova, A. V.
Summary The red fox (Vulpes vulpes) demonstrates a variety of coat colors including platinum, a common phenotype maintained in farm‐bred fox populations. Foxes heterozygous for the platinum allele have a light silver coat and extensive white spotting, whereas homozygosity is embryonic lethal. Two KIT transcripts were identified in skin cDNA from platinum foxes. The long transcript was identical to the KIT transcript of silver foxes, whereas the short transcript, which lacks exon 17, was specific to platinum. The KIT gene has several copies in the fox genome: an autosomal copy on chromosome 2 and additional copies on the B chromosomes. To identify the platinum‐specific KIT sequence, the genomes of one platinum and one silver fox were sequenced. A single nucleotide polymorphism (SNP) was identified at the first nucleotide of KIT intron 17 in the platinum fox. In platinum foxes, the A allele of the SNP disrupts the donor splice site and causes exon 17, which is part of a segment that encodes a conserved tyrosine kinase domain, to be skipped. Complete cosegregation of the A allele with the platinum phenotype was confirmed by linkage mapping (LOD 25.59). All genotyped farm‐bred platinum foxes from Russia and the US were heterozygous for the SNP (A/G), whereas foxes with different coat colors were homozygous for the G allele. Identification of the platinum mutation suggests that other fox white‐spotting phenotypes, which are allelic to platinum, would also be caused by mutations in the KIT gene.